Back to the Future-Cardiovascular Imaging From 1966 to Today and Tomorrow - Wintersperger, Bernd J; Alkadhi, Hatem; Wildberger, Joachim E (Investigative radiology, 2025)
This article, on the 60th anniversary of the journal Investigative Radiology, a journal dedicated to cutting-edge imaging technology, discusses key historical milestones in CT and MRI technology, as well as the ongoing advancement of contrast agent development for cardiovascular imaging over the past decades. It specifically highlights recent developments and the current state-of-the-art technology, including photon-counting detector CT and artificial intelligence, which will further push the boundaries of cardiovascular imaging. What were once ideas and visions have become today's clinical reality for the benefit of patients, and imaging technology will continue to evolve and transform modern medicine.